INTEGRATION OF ISLAMIC PSYCHOTHERAPY AND MENTAL HEALTH: THE TAZKIYATUN NAFS MODEL IN THE CONTEXT OF THE GONTOR ISLAMIC BOARDING SCHOOL COMMUNITY - Malikah (EDUCATIONE, 2026)
This study focuses on the high prevalence of mental health problems among students at the Gontor Islamic Boarding School who face limitations in conventional psychotherapy approaches that are not in line with their cultural and spiritual values. The gap is the lack of research integrating Islamic-based psychotherapy, especially the concept of Tazkiyatun Nafs, in Islamic boarding school education. The purpose of this study is to examine and develop a model for applying Tazkiyatun Nafs as a psychotherapeutic approach in the Gontor santri community. A qualitative approach with an intrinsic case study design was used in this study, which involved in-depth interviews, participatory observation, and document analysis. The results of the study show that the application of Tazkiyatun Nafs through the practices of muhasabah, mujāhadah, and riyādhah has been proven effective in improving the mental well-being of santri and can be implemented in the pesantren curriculum. Further discussion reveals that Islamic principles such as tawakkul and muhasabah function as effective coping mechanisms in overcoming anxiety and stress. This study makes a significant contribution to the development of an Islamic-based psychotherapy model that is relevant to the cultural and spiritual needs of Muslim communities.